2022
DOI: 10.3390/antibiotics11060706
|View full text |Cite
|
Sign up to set email alerts
|

Are Virulence and Antibiotic Resistance Genes Linked? A Comprehensive Analysis of Bacterial Chromosomes and Plasmids

Abstract: Although pathogenic bacteria are the targets of antibiotics, these drugs also affect hundreds of commensal or mutualistic species. Moreover, the use of antibiotics is not only restricted to the treatment of infections but is also largely applied in agriculture and in prophylaxis. During this work, we tested the hypothesis that there is a correlation between the number and the genomic location of antibiotic resistance (AR) genes and virulence factor (VF) genes. We performed a comprehensive study of 16,632 refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 40 publications
2
25
0
Order By: Relevance
“…Resistance to disinfectants reveals a worrying effect of the increasing use of products on the adaptive and evolutionary response of microbial communities. This result agrees with our previous research on a dataset consisting of over 16,000 reference bacterial genomes that showed enrichment of the mobilome with genes encoding resistance to disinfectants [ 33 ]. These high levels of resistance genes and the fact that they tend to be encoded in the mobilome highlights, on the one hand, the selective pressure effect that bacteria and microbiomes are subjected to, but also the epidemic potential of these newly acquired traits.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Resistance to disinfectants reveals a worrying effect of the increasing use of products on the adaptive and evolutionary response of microbial communities. This result agrees with our previous research on a dataset consisting of over 16,000 reference bacterial genomes that showed enrichment of the mobilome with genes encoding resistance to disinfectants [ 33 ]. These high levels of resistance genes and the fact that they tend to be encoded in the mobilome highlights, on the one hand, the selective pressure effect that bacteria and microbiomes are subjected to, but also the epidemic potential of these newly acquired traits.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies show that sediments are biomes that possess a great diversity of antibiotic-resistance genes [ 32 ]. A comprehensive study of bacterial genomes reveals that, at the genomic level, the most frequent resistance genes present are those conferring resistance to beta-lactams, sulfonamide, quinolones, and only then to macrolides and tetracycline, and that resistance to oxazolidinone is rare [ 33 ]. This profile at the genomic level is different from that found in the metagenomes of aquaculture sediments, thus revealing a specific profile of these metagenomes.…”
Section: Discussionmentioning
confidence: 99%
“…The similar burden of VFGs detected in CONT and TREAT cattle on days 3, 7, and 14 suggests that antibiotic treatment was unlikely to be a practice promoting VFGs dissemination through pathogen enrichment in the gastrointestinal tract of cattle. As the entire host’s microbiome is under antibiotics’ selective pressure, not only bacterial pathogens but also the association between ARGs and pathogenic VFGs weakens [ 62 ]. Moreover, the increase in the number of reads aligned to ARGs conferring resistance to tetracyclines observed after antibiotic administration in TREAT cattle did not correlate with an increase in VFGs, suggesting that those tetracycline-resistance genes were enriched in commensal bacteria that may act as a reservoir of ARGs [ 51 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…ICEs are also known as conjugative transposons that are crucial for horizontal gene transfer between cells, and they can carry insertion sequences and/or transposons, integrases, and the relaxase enzyme, which is critical for conjugation. Antimicrobial resistance (AMR) is continuously evolving and the genes are transferred horizontally through plasmids [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%